Colorectal Cancer Liver Metastasis Trends in the Kingdom of Saudi Arabia - Hassanain, Mazen (Saudi J Gastroenterol, 2016)
BACKGROUND/AIM: To elucidate colorectal cancer (CRC) disease patterns, demographics, characteristics, stage at presentation, metastases, and survival rates of patients, particularly those with liver metastases, at our center as the first report from the Kingdom of Saudi Arabia. PATIENTS AND METHODS: We performed a retrospective, single-center database study based on the histological diagnosis of CRC in patients seen at the King Khalid University Hospital between 2007 and 2011. RESULTS: 427 cases of CRC with a mean age at diagnosis of 55.47 ± 12.85 years, out of which 96% were resected. Stage II was predominant at presentation, followed by both stage III and IV, with the remainder being stage I. One hundred patients had distant metastases, of which the liver was the only location in 54 patients. Mean survival was 3.0 years. Overall survival rates for CRC patients with liver metastases who underwent resection were 30% at 2 years and 17% at 5 years, and the mean survival rate was 1.4 years. CONCLUSIONS: Both the mean survival rate of our CRC patients with resectable liver metastases and the 5-year survival rate of these patients are lower than global averages. This discrepancy is likely due to late diagnoses rather than more aggressive disease.